The Mediating Effects of Switching Costs on the Relationship between Service Quality, Customer Satisfaction and Customer Loyalty: A Study in Retail Banking Industry in Vietnam - Ngo, Vu Minh; Phan, Quyen Phu Thi; Nguyen, Ninh Van; Minh Vu, Hieu (International Journal of Supply Chain Management, 2019)
This paper develops and empirically tests the mediating role of switching costs in service quality - loyalty and satisfaction-loyalty relationships. Especially, different types of switching costs are tested separately providing more insights into their roles. A research model about the interrelationships between service quality, customer satisfaction, switching costs and customer loyalty is developed. Based on this model, a survey is conducted with retail banking customers, with and 261valid respondents. The hypotheses are then proposed and tested using Structural equation modeling technique (SEM). The analysis reveals that: positive switching cost is a significant mediator for both service quality-loyalty and satisfaction-loyalty relationships, while negative switching cost only mediates the service quality-loyalty relationship. These findings suggest that building and managing switching costs are necessary following-up steps after customer satisfaction for achieving long-term customer loyalty.